New data on the age and geographic distribution of Neoproterozoic plutons near Saint John, New Brunswick - Currie, K.; McNicoll, V. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1999)
New U-Pb zircon and titanite ages for four plutons from the Brookville and Mascarene blocks of the Saint John region suggest that the age distribution of Neoproterozoic intrusions in the Mascarene block resembles that in the Caledonia block, with older plutons emplaced at -630-620 Ma (Brittain Creek, 625 ± 2 Ma, U-Pb zircon and titanite; Lingley, 629.3 ± 0.9 Ma, U-Pb zircon), and younger plutons emplaced at about 550 Ma. Older plutons are more fractured and altered than younger ones, but not everywhere more strongly foliated. Within the Brookville block, the Hanson Stream pluton gives an age of 532 +1/-3 Ma (U-Pb zircon), demonstrating that "Ar/^Ar ages as young as ca. 518 Ma from this pluton (Dallmeyer and Nance 1992) indicate post-emplacement disturbance. The A-type Harvey Hill pluton, previously thought to be the youngest pluton in the Brookville block, gave a U-Pb zircon age of 544 ± 4 Ma, similar to mat of the geochemicalry similar Bonnell Brook pluton of the Caledonia block. Combined with presence of a distinctive Cambro-Ordovician siliciclastic cover (Saint John GroupX these dates indicate mat the Mascarene and Caledonia blocks originated in the same continental fragment Western parts of the Brookville and Mascarene blocks were affected by a Cambrian thermal event (520-510 Ma), which may also be represented in the Caledonia block. Tectonic models based on these data suggest that the Saint John region underwent repeated subduction in Neoproterozoic time and diverse transcurrent movements from Silurian to Carboniferous time.